Acute thrombosis of the great arterial trunks and biliary disorders - Praderi, Raúl; Ormaechea, Carlos; Harretche, Martín; Mazza, Milton (Cirugía del Uruguay, 2020)
The paper contains an account of three observations of thrombosis in the large arterial trunks ( aorta, subclavian and iliac) in patients with concomitant biliary diseases ( biliary ileus, pancreatic cancer with lithiasis of the gall bladder and acute cholecystitis). It also describes two cases of thrombosis in the humeral and femoral arteries in patients with visceral tuberculosis treated by corticoids. The pathogenic connection between both types of diseases as a result of an increase of the thrombophilia due to the prior abdominal disease, is pointed out.